Candlenut Tree Management on People Forest in Tanah Pinem Subdistrict, Dairi Regency, Indonesia - Tetty Pryska Herawaty Sihombing; Hardjanto; Nurheni Wijayanto (Institut Pertanian Bogor (IPB University), 2013)
Candlenut tree is one of the multipurpose tree species because almost all parts of the plant can be utilized. The candlenut trees grow and are distributed in all provinces of Indonesia. Tanah Pinem in Dairi Regency is one of the candlenut-producer area. The objectives of this study were to learn and describe the management of candlenut tree in Tanah Pinem Subdistrict. The research was conducted with survey method by collecting data in the field. Primary data were obtained through structured interviews, while secondary data were obtained from relevant institutions and previous researches. The data were analyzed and described to learn how the community manage the candlenut tree and the condition at that time. The results showed that the candlenut tree is one of the plants that are beneficial because it can be a source of income for the community and play a role in safeguarding the environmental conditions of Tanah Pinem subdistrict. However, the management of candlenut tree was not intensive. Area size and production of candlenut tree tended to decrease each year. About 90% of Tanah Pinem subdistrict topography are steep and very steep, and it is necessary to replant the land with trees such as candlenut to protect the land from erosion and landslide hazards.